Comments on Piazzesi and Schneider's "Bond positions, expectations, and the yield curve" - Jon Faust (Federal Reserve Bank of Atlanta, 2008)
This working paper comments on Monika Piazzesi and Martin Schneider's 'Bond Positions, Expectations, and the Yield Curve', delivered at the Fiscal Policy and Monetary/Fiscal Policy Interactions conference held at the Atlanta Fed on April 19-20, 2007.
Keywords: 330; expectations; surveys; interest rates; portfolio choice; asset positions; term structure; yield curve